Childhood trauma as a predictor of reoffending in a Northern Irish probation sample. (November 2019) - Dalsklev, Madeleine; Cunningham, Twylla; Travers, Áine; McDonagh, Tracey; Shannon, Ciaran; Downes, Ciara; Hanna, Donncha
Abstract: Background: It is well-documented that there is a high prevalence rate of childhood trauma experiences among the prison population, and studies have found a link between childhood trauma and later acts of violence. Objective: The aim of the current study was to investigate whether childhood trauma (i.e., physical, sexual, emotional abuse and physical neglect) among offenders who have served a life sentence in Northern Ireland was associated with general and violent reoffending patterns. The study also explored the relationship between childhood trauma resulting from the sectarian conflict "The Troubles" in the region and its impact on reoffending. Method: The casefiles of 100 offenders were coded for trauma experiences and official reoffending data was extracted. Logistic regression analysis was performed to explore the relationship between trauma and reoffending. Results: The most common form of childhood trauma were emotional abuse and/or emotional neglect ( n = 43), conflict-related trauma ( n = 43) and physical abuse ( n = 40). Only age (OR .91) and conflict-related trauma (OR 5.57) emerged as significant predictors ( p < .05) of general reoffending at any time post release. Similarly, only age (OR .92) and conflict-related trauma (OR 4.57) emerged as significant predictors ( p < .05) of violent reoffending. Although it did not reach significance ( p = .09), childhood physical abuse was related to an increase in the odds of violently reoffending, of a large magnitude (OR 4.09). Conclusions: Conflict-related trauma significantly predicted general and violent reoffending among offenders with previous violent convictions.